Predatory behaviour of alpine (Ichthyosaura alpestris) and smooth (Lissotriton vulgaris) newts towards conspecific and heterospecific eggs and larvae. Issue 4 (4th July 2017) - Mettouris, Onoufrios; Giokas, Sinos
Abstract : Consumption of conspecific and heterospecific eggs and larvae is common in many animal taxa, including many amphibians. Adult newts (Amphibia Urodela) often co-occur temporally and spatially with conspecific and heterospecific newt eggs and larvae, and adult individuals may benefit from their consumption, but little is known on the degree of discrimination in the newts' predatory behaviour towards them. We performed two laboratory experiments to examine whether adult male and female alpine, Ichthyosaura alpestris (Laurenti 1768), and smooth, Lissotriton vulgaris (Linnaeus 1758), newts discriminate between conspecific and heterospecific eggs and larvae in their predatory behaviour. In our study, eight out of 64 newts succeeded in consuming eggs, although 3 times as many attacked them. We found no differences in predatory behaviour towards conspecific and heterospecific eggs, or between males and females in either species. Similarly, we found no evidence for the occurrence of discriminative predatory behaviour towards conspecific and heterospecific larvae. In our experiments the criterion for whether a newt would consume a prey item (egg or larva) was not the prey's identity (species), but the newts' ability to detect, capture and/or ingest it. Our results suggest that newts of both species follow an opportunistic foraging strategy, consuming whatever prey of appropriate size they manage to capture.